The appraisal of antioxidant properties of two Malaysian herbs Cosmos caudatus and Piper sarmentosa - Shahrim, Anis Suraya; Ahmad Nazri, Norain Nabila; Harun, Aiza; Abdul Aziz, Noorshilawati; Daud, Shaari (GADING Journal of Science and Technology, 2024)
Nowadays the impacts on the use of natural ingredients in modern medicine cannot be denied as they exhibit amazing antioxidant properties. Thus, the study aims to investigate the antioxidant properties of Cosmos caudatus and Piper sarmentosum leave extract using thin layer chromatography (TLC) dot blot assay and 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging assay. The dot blot assay method was reported for the first time for both species. The crude extracts of C. caudatus and P. sarmentosum leaves extract were prepared through consecutive maceration using hexane, ethyl acetate, acetone and methanol. According to TLC dot blot assay, the methanol extract of P. sarmentosum inhibit the DPPH radical at a concentration of 0.30 mg/ml while acetone extract of C. caudatus inhibit the DPPH radical at a concentration of 0.012 mg/ml. The radical scavenging activities for both species show concentration dependent manner. Methanol extract of P. sarmentosum and acetone extract of C. caudatus show the lowest IC50 with 32.009 μg/ml and 14.12 μg/ml, respectively for DPPH assay. Therefore, the polar extracts of both species are known to be the most promising source of antioxidant agent compared to less polar extract. The results may be applicable to medical and pharmaceutical industries as they provide basic scientific data for the development of new natural medicines.